CFD‐ and Bernoulli‐based pressure drop estimates: A comparison using patient anatomies from heart and aortic valve segmentation of CT images. Issue 6 (25th April 2017) - Weese, Jürgen; Lungu, Angela; Peters, Jochen; Weber, Frank M.; Waechter‐Stehle, Irina; Hose, D. Rodney
Abstract : Purpose: An aortic valve stenosis is an abnormal narrowing of the aortic valve (AV). It impedes blood flow and is often quantified by the geometric orifice area of the AV (AVA) and the pressure drop (PD). Using the Bernoulli equation, a relation between the PD and the effective orifice area (EOA) represented by the area of the vena contracta (VC) downstream of the AV can be derived. We investigate the relation between the AVA and the EOA using patient anatomies derived from cardiac computed tomography (CT) angiography images and computational fluid dynamic (CFD) simulations. Methods: We developed a shape‐constrained deformable model for segmenting the AV, the ascending aorta (AA), and the left ventricle (LV) in cardiac CT images. In particular, we designed a structured AV mesh model, trained the model on CT scans, and integrated it with an available model for heart segmentation. The planimetric AVA was determined from the cross‐sectional slice with minimum AV opening area. In addition, the AVA was determined as the nonobstructed area along the AV axis by projecting the AV leaflet rims on a plane perpendicular to the AV axis. The flow rate was derived from the LV volume change. Steady‐state CFD simulations were performed on the patient anatomies resulting from segmentation. Results: Heart and valve segmentation was used to retrospectively analyze 22 cardiac CT angiography image sequences of patients with noncalcified and (partially) severely calcified tricuspid AVs. Resulting AVAs were in the range of 1–4.5 cm 2 and ejection fractions (EFs) between 20 and 75%. AVA values computed by projection were smaller than those computed by planimetry, and both were strongly correlated ( R 2 = 0.995). EOA values computed via the Bernoulli equation from CFD‐based PD results were strongly correlated with both AVA values ( R 2 = 0.97). EOA values were ∼10% smaller than planimetric AVA values. For EOA values < 2.0 cm 2, the EOA was up to ∼15% larger than the projected AVA. Conclusions: The presented segmentation algorithm allowed to construct detailed AV models for 22 patient cases. Because of the crown‐like 3D structure of the AV, the planimetric AVA is larger than the projected AVA formed by the free edges of the AV leaflets. The AVA formed by the free edges of the AV leaflets was smaller than the EOA for EOA values < 2.0 cm 2 . This contradiction with respect to previous studies that reported the EOA to be always smaller or equal to the geometric AVA is explained by the more detailed AV models used within this study.